Advanced Ceramic and Metallic Coating and Thin Film Materials for Energy and Environmental Applications - Zhang, Jing.; Jung, Yeon-Gil.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book explores the recent developments, perspectives on future research, and pertinent data from academia, industry, and government research laboratory to discuss fundamental mechanisms as well as processing and applications of advanced metallic and ceramic thin film and coating materials for energy and environmental applications. It is a platform to disseminate the latest research progress related to processing, characterization, and modelling. The authors address both thermal barrier and environmental coatings; magnetic and thermoelectric materials; and solar cell and solid oxide fuel cell materials. It is appropriate supplementary reading for students and primary reading for researchers in materials science and engineering. .
Overview of Advanced Ceramic and Metallic Coatings for Energy and Environmental Applications -- Processing and Characterization of Coating and Thin Film Materials -- Magnetic Materials -- Thermoelectric Materials -- Solar Energy and Solar Cell Materials -- Solid Oxide Fuel Cell Materials -- Modeling and Simulation of Energy Materials and Processes.
Keywords: Microtechnology; Microelectromechanical systems; Surfaces (Technology).; Thin films; Energy policy; Energy and state; Electric power production; Environmental engineering; Biotechnology; Bioremediation; Microsystems and MEMS; Surfaces, Interfaces and Thin Film; Energy Policy, Economics and Management; Electrical Power Engineering; Mechanical Power Engineering; Environmental Engineering/Biotechnology.